Socioeconomic factors and regional differences in mental disorder-based disability pensioning in Finland - T. Karolaakso; R. Autio; T. Näppilä; K. Nurmela; H. Leppänen; P. Rissanen; M. Tuomisto; S. Karvonen; S. Pirkola (European Psychiatry, 2022)
Introduction Prior literature has indicated low socioeconomic status (SES) and regional differences as epidemiological risk factors for disability pension (DP) due to mental disorders.